THE INFLUENCE OF FIELDWORK PRACTICES, SELF-EFFICACY, AND THE FAMILY ENVIRONMENT ON THE WORK READINESS OF STUDENTS OF CLASS XII SMK FINANCIAL ACCOUNTING EXPERTISE PROGRAM AND INSTITUTIONS: PENGARUH PRAKTIK KERJA LAPANGAN, EFIKASI DIRI, DAN LINGKUNGAN KELUARGA TERHADAP KESIAPAN KERJA SISWA KELAS XII SMK PROGRAM KEAHLIAN AKUNTANSI KEUANGAN DAN LEMBAGA - Syifana Dzikri Maulidy; Sri Zulaihati; Ati Sumiati (Yayasan Education and Social Center, 2022)
Work readiness is one of the initial basic things that SMK graduates must prepare in preparing themselves in the work environment. This research aims to find about the effect of field work practices, self-efficacy, and the family environment on the work readiness of class XII students of vocational school of financial accounting and institutional accounting program in pasar minggu. This study uses survey and questionnaire as research methodology. The used population for this study is students of vocational school of financial accounting and institutional accounting program in pasar minggu; SMKN 25 and SMKN 8 Jakarta. this study uses 175 people with proportional random sampling technique as sample. the coefficient of determination in this study was 12.8% with the results showing that there was an influence field work practices, self-efficacy, and the family environment on the work readiness, the rest was influenced by other variables that were not studied